2021
DOI: 10.1111/epi.17039
|View full text |Cite
|
Sign up to set email alerts
|

A web‐based algorithm to rapidly classify seizures for the purpose of drug selection

Abstract: Objective: To develop and validate a pragmatic algorithm that classifies seizure types, to facilitate therapeutic decision-making. Methods: Using a modified Delphi method, five experts developed a pragmatic classification of nine types of epileptic seizures or combinations of seizures that influence choice of medication, and constructed a simple algorithm, freely available on the internet. The algorithm consists of seven ques-K E Y W O R D S algorithm, classification, epilepsy, seizure, web-based application K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A great motivation for the research in this sector derives from the will to speed up the process that leads the patient to be considered a candidate for surgery and also to find alternative types of information that healthcare professionals can collect more easily without necessarily requiring highly specialized diagnostic machinery. Recently, many research projects aimed at developing decision support systems that could provide a more accurate classification of seizures relying on questionnaires [19]. Studies based on self-reported questionnaires are highly dependent on patients’ willingness to personally contribute to the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great motivation for the research in this sector derives from the will to speed up the process that leads the patient to be considered a candidate for surgery and also to find alternative types of information that healthcare professionals can collect more easily without necessarily requiring highly specialized diagnostic machinery. Recently, many research projects aimed at developing decision support systems that could provide a more accurate classification of seizures relying on questionnaires [19]. Studies based on self-reported questionnaires are highly dependent on patients’ willingness to personally contribute to the study.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the epilepsy field, literature reports different tools developed as answers to specific needs. For instance, the authors of [19] present a decision support system that exploits 7 questions addressed to the patients providing an accurate classification of seizure types. Epifinder [20] is a clinical decision support system for epilepsy diagnosis which, given some keywords extracted from the semiological descriptions of the seizures, returns the probability to being affected by epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Beniczky and colleagues have tackled this problem with a rapid algorithmic web tool (EpiPick.org) intended to provide clinicians, especially in underserved regions, instant expert advice. Using iterative Delphi methods, they had 2 goals: 1) To develop a simple algorithm classifying seizure types, 4 and 2) To determine optimal antiseizure medication (ASM) choices for each seizure type. 5,6 For the first goal (classifying seizure types), 5 expert epileptologists met to agree upon the minimum number of distinct seizure types that would influence treatment decisions.…”
Section: Commentarymentioning
confidence: 99%
“…Following the publication of the algorithm, we have further validated the app in three studies. In a large, multicenter, prospective study, 2 we validated the first part of the algorithm, which classifies seizure types to facilitate therapeutic decision-making. Agreement between the algorithm and the expert classification was 83.2% [95% confidence interval (CI) 78.6%-87.8%], with an agreement coefficient (AC1) of 0.82 (95% CI 0.77-0.87), indicating almost perfect agreement.…”
Section: E T T E R the Epipick Algorithm To Select Appropriate Antise...mentioning
confidence: 99%
“…Agreement between the algorithm and the expert classification was 83.2% [95% confidence interval (CI) 78.6%-87.8%], with an agreement coefficient (AC1) of 0.82 (95% CI 0.77-0.87), indicating almost perfect agreement. 2 In another study 3 we investigated the agreement among experts in selecting an ASM as initial monotherapy and used their choices to validate the app. The percent agreement between the highest ranked selections of the app and the expert selections was 73% (95% CI 64%-82%).…”
Section: E T T E R the Epipick Algorithm To Select Appropriate Antise...mentioning
confidence: 99%